Islamic Law Legislation in Indonesia: Anomalies of the Relationship between Political Configuration and Zakat Legal Product during the Reform Era - Ali Murtadho Emzaed; Ibnu Elmi AS Pelu; Shakhzod Tokhirov (Al-Manahij: Jurnal Kajian Hukum Islam, 2023)
This article discusses the anomaly of democratic political configuration relation that produces conservative zakat law product in Law Number 23 Year 2011 on Zakat Management. Zakat law has experienced the positivation of Islamic law through what is called the legislative process in the House of Representatives. Through its stipulation, it actually led to rejection from Muslim civil society groups. This rejection is an indication that the law is not responsive to civil society. This research is normative juridical with a political approach to law that places legislation as a political product. Edward W. Soja’s spatial justice theory is used to analyze this issue. The findings of this research are, first, the anomaly of political configuration relations towards zakat law products occurs because of the still entrenched character of executive dominance in making zakat law in the DPR. Second, to produce a responsive law, it must provide space for spatial justice through the participation of Islamic civil society in making zakat law.